Therapeutic prospects of ceRNAs in COVID-19 - Liu, Lin; Zhang, Yao; Chen, Yu; Zhao, Yueshui; Shen, Jing; Wu, Xu; Li, Mingxing; Chen, Meijuan; Li, Xiaobing; Sun, Yuhong; Gu, Li; Li, Wanping; et al. (Frontiers in Cellular and Infection Microbiology, 2022)
Since the end of 2019, COVID-19 caused by SARS-CoV-2 has spread all over the world, and the new coronavirus is still in the exploration stage. Currently, immunotherapy, cell therapy, antiviral therapy and Chinese herbal medicine have been applied to the clinical treatment of the new coronavirus, there is still a need for more efficient and safe drugs to control the progress of the new coronavirus. LncRNA, miRNA, circRNA may provide new therapeutic targets for new coronavirus treatment. This paper first reviews the research progress of COVID-19 in the respiratory, immune, digestive, circulatory, urinary, reproductive, and nervous systems, and then reviews the various systems and potential therapeutic targets of lncRNAs, miRNAs, and circRNAs in patients with COVID-19. Then, the current research on ceRNA (lncRNA-miRNA-mRNA and circRNA-miRNA-mRNA) in SARS-CoV-2 was summarized. Finally, we predicted the possible therapeutic targets of four lncRNAs, lncRNA MALAT1, lncRNA NEAT1, lncRNA TUG1 and lncRNA GAS5 in COVID-19. It is worth noting that the role of PTEN gene in the ceRNA network predicted by lncRNA MALAT1 and lncRNA TUG1 may help in the discovery and clinical treatment of effective drugs for COVID-19.